2018
DOI: 10.1111/eip.12559
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence in first‐episode psychosis patients in Singapore

Abstract: Medication adherence is prevalent in FEP and associated with a variety of factors. This study supports the use of culturally appropriate interventions in addressing barriers to adherence. Further studies would need to be done to address specific factors affecting adherence outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
0
10
0
2
Order By: Relevance
“…Nonadherence to treatment leads to frequent hospitalizations and poor prognosis, which increases not only the burden of care on the family, but also the individual's level of burnout, disability, and the likelihood of suicide or harm to others (Tan et al, 2019). In addition, criminal activity among patients who do not adhere to treatment reinforces public stereotypes about these individuals, leading to a vicious cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Nonadherence to treatment leads to frequent hospitalizations and poor prognosis, which increases not only the burden of care on the family, but also the individual's level of burnout, disability, and the likelihood of suicide or harm to others (Tan et al, 2019). In addition, criminal activity among patients who do not adhere to treatment reinforces public stereotypes about these individuals, leading to a vicious cycle.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of treatment adherence is associated with poor clinical and functional outcomes. Moreover, a high number of FEP patients are non-adherent to treatment at 12-month follow-up, which increases the risk of relapse and rehospitalisations [ 2 , 11 , 54 , 55 ]. Our results, according to other studies, revealed that psychoeducational intervention could be crucial for improving adherence to medication and illness course, and that clinical outcomes of patients not only depend on initial treatment but also on continued adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a significant association between aggression and duration of untreated illness. The multi-ethnic population, low prevalence of alcohol and other substance use disorders ( 30 , 31 ), relatively low treatment gap ( 32 ) and high medication compliance ( 33 ), emphasize the need for local data in Singapore. Thus, the current study aims to (i) examine underlying factor structure of the Buss-Perry Aggression Questionnaire (BPAQ) and (ii) explore the socio-demographic and clinical associations (symptom severity, drug and alcohol use) of aggression as assessed by BPAQ among patients with schizophrenia and related psychoses in a multi-ethnic Asian population.…”
Section: Introductionmentioning
confidence: 99%